2011
DOI: 10.1183/09031936.00072210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atrial septostomy on the survival of patients with severe pulmonary arterial hypertension

Abstract: Atrial septostomy (AS) is a palliative treatment for right ventricular failure from severe pulmonary arterial hypertension (PAH). We sought to investigate the effect of AS, alone or combined with PAH-specific pharmacotherapy, on the survival of patients with PAH.We performed a retrospective analysis of the functional and haemodynamic changes in patients with PAH following AS, and long-term survival characteristics for the whole group and separately for the subgroup who received post-procedural pharmacotherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 28 publications
0
101
0
1
Order By: Relevance
“…Another potential strategy to improve outcome is to use BAS in combination with PAH-specific therapies. A recent study of 34 patients with severe PAH treated with BAS reported haemodynamic and symptomatic improvement in most patients, with significantly better survival in those patients who also received PAH-specific therapies compared with those who received BAS alone (median 83 months, 95% CI 57-109 months versus 53 months, 95% CI 39-67 months, respectively; p50.010) [54].…”
Section: Surgical Interventionmentioning
confidence: 99%
“…Another potential strategy to improve outcome is to use BAS in combination with PAH-specific therapies. A recent study of 34 patients with severe PAH treated with BAS reported haemodynamic and symptomatic improvement in most patients, with significantly better survival in those patients who also received PAH-specific therapies compared with those who received BAS alone (median 83 months, 95% CI 57-109 months versus 53 months, 95% CI 39-67 months, respectively; p50.010) [54].…”
Section: Surgical Interventionmentioning
confidence: 99%
“…In line with other reports, there was a significant increase in cardiac index, resulting in an increase in systemic oxygen transport [2][3][4]. Unfortunately, a subsequent size reduction or spontaneous closure of the defect has been observed in many reports requiring repeat BAS procedures [5,6]. To avoid this problem, Micheletti et al [7] implanted a custom-made fenestrated atrial septal device at the conclusion of BAS procedure to maintain the atrial septum opened.…”
mentioning
confidence: 79%
“…Guidelines do not comment on atrioseptostomy in the case of RV overload in PH-CHD. However, this procedure is described in other types of pulmonary arterial hypertension with acceptable results [21,22]. The procedure resulted in enhanced systemic oxygen delivery and short-term clinical improvement.…”
Section: Discussionmentioning
confidence: 99%